La componente estética de la justicia social integral : una aproximación a la obra arquitectónica de la Fundación de ayuda social María Eva Duarte de Perón (1948-1952) - Amado Silvero, Florencia (2023)
On October 17, 1945, the rules of the game of Argentine politics changed forever. From the arrival of Juan Domingo Perón to the Argentine presidency, and Eva Duarte, to the field of social action; argentine society underwent transcendental changes that would be present in all national cultural production, including architecture. In this way, most of argentine society is divided, grouping behind two political banners: peronismo and anti-peronismo. Both groups, diverse, heterogeneous and even contradictory, will make up the two faces of argentine society, and it is possible to assign aesthetic characteristics to each.\nLikewise, and for the first time in argentine history, a "first lady" takes on importance as a political actor with its own weight, articulating and executing its power through its own institution, which at times will function privately, in others parastatally, from time to time complementary, without ever losing its independent character, and in an innovative way that will bear its name.\nThe Eva Perón Foundation and its director entered the argentine scene at the end of 1948, leaving charity behind to make way for comprehensive social justice; where the aesthetic component, headed by the neocolonial, provokes an architectural dialogue, not without friction, with several fronts. On the one hand, with its otherness, the vestiges of the Charity Society with the ladies of the oligarchy and a combative anti-peronismo and on the other, with members of the peronist government itself, ministers and secretaries, possessors of a strong misogyny, who do not see with good eyes the vertiginous rise of María Eva Duarte de Perón in argentine politics, which will put in check the forms and times of the old politics in matters of social assistance.